Four new species of Caraipa (Calophyllaceae) from the Amazon basin and the Guiana Shield - Cabral, Fernanda Nunes; Bittrich, Volker; Estanislau Do Amaral, Maria Do Carmo (Phytotaxa, 2016)
Four new species of Caraipa (Calophyllaceae) are described and illustrated: Caraipa balbinensis, endemic to Balbina (Presidente Figueiredo, Amazonas, Brazil), C. caespitosa growing in savannah and white-sand vegetation in Roraima and Amazonas (Brazil), Guainía (Colombia) and Amazonas (Venezuela), C. davilae, an endemic species of Loreto (Peru), and C. macrocarpa, an endemic species to Guyana. Morphological comparisons with the similar taxa are provided for each new species: C. balbinensis can be distinguished from C. heterocarpa by its longer leaves and petioles, and its slightly rugulose fruit surface; C. caespitosa can be separated from C. grandifolia and C. longipedicellata by its distinguished habit, and its smaller leaves and inflorescences; C. davilae differs from C. balbinensis and C. grandifolia by its dense indument on the abaxial leaf surface, and its rugulose and concave fruit valves; and C. macrocarpa can be distinguished from C. punctulata by its large, glabrous and rugulose fruits.